Crystal structure of 6-bromo-7-fluoro-4-oxo-4H-chromene-3-carbaldehyde - Yoshinobu Ishikawa (Acta Crystallographica Section E: Crystallographic Communications, 2015)
In the title compound, C10H4BrFO3, a brominated and fluorinated 3-formylchromone derivative, all atoms are essentially coplanar (r.m.s. deviation of 0.025 Å for the non-H atoms), with the largest deviation from the least-squares plane [0.050 (6) Å] being for a benzene-ring C atom. In the crystal, molecules are linked through stacking interactions [centroid–centroid distance between the benzene and pyran rings = 3.912 (4) Å], C—H...O hydrogen bonds and short C...O contacts [2.865 (7) Å]. Unsymmetrical halogen...halogen interactions between the bromine and fluorine atoms [Br...F = 3.116 (4) Å, C—Br...F = 151.8 (2), C—F...Br = 154.1 (4)°] are also formed, giving a meandering two-dimensional network propagating in the (041) plane. A comparison with related structures is made and the various types of weak interactions are ranked in importance.